2021
DOI: 10.1097/hs9.0000000000000640
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics, Treatment, and Outcomes of Post-transplant Lymphoproliferative Disorders: A Single-institution Experience Using 2017 WHO Diagnostic Criteria

Abstract: The World Health Organization Classification of Tumours of Haematopoietic and Lymphoid Tissues (WHO 2017) included updated criteria for diagnosis and classification of post-transplant lymphoproliferative disorders (PTLDs). This study evaluated the clinicopathologic spectrum using WHO 2017 criteria and adult PTLD patients’ outcomes over 30 years between 1987 and 2017 at Mayo Clinic (Rochester, MN). Patients were retrospectively reviewed for clinical features, outcomes, and diagnostic path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 40 publications
(162 reference statements)
0
19
0
Order By: Relevance
“…In a recent large single-institution study, CHL PTLD had the best prognosis of all the destructive type PTLD with a 2-year point estimate overall survival of 1.00 versus monomorphic B cell PTLD (0.62) and polymorphic PTLD (0.69). [68] This is in contrast to what has been reported in OIIA-LPD in patients with rheumatic diseases where overall survival of Hodgkin-type LPD was similar to DLBCL-type, but PFS was worse for the Hodgkin cases. [74]…”
Section: Classic Hodgkin Lymphoma Ptldmentioning
confidence: 62%
See 1 more Smart Citation
“…In a recent large single-institution study, CHL PTLD had the best prognosis of all the destructive type PTLD with a 2-year point estimate overall survival of 1.00 versus monomorphic B cell PTLD (0.62) and polymorphic PTLD (0.69). [68] This is in contrast to what has been reported in OIIA-LPD in patients with rheumatic diseases where overall survival of Hodgkin-type LPD was similar to DLBCL-type, but PFS was worse for the Hodgkin cases. [74]…”
Section: Classic Hodgkin Lymphoma Ptldmentioning
confidence: 62%
“…The published literature is not consistent in terms of whether patients with polymorphic PTLD have a better prognosis than those with monomorphic PTLD with a recent large study reporting similar overall survivals (see below). [68]…”
Section: Polymorphic Ptldmentioning
confidence: 99%
“…11 cases (5.6%) of polymorphic PTLD, which is less than previously reported (3,26,37,42). A more recent report noted a similar rate, with 5.7% polymorphic PTLD in a single center analysis of 227 adult PTLD after SOT (14). Tsai et al also reported that PTLD morphology has changed over the past 3 decades, with a gradual increase in the number of monomorphic PTLD and a steady number of polymorphic PTLD (38).…”
Section: Discussionmentioning
confidence: 86%
“…However, we observed a significant relation between EBV status and OS in PT-DLBCL, with clinically meaningful improved survival in EBV(-) PT-DLBCL compared to EBV(+) PT-DLBCL (8.8 years versus 2.5 years, respectively). Previous reports have shown conflicting results on the relation between EBV status and OS (13,14,18,25,50,57,58).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation